Визначення загальних принципів організації надійної бездротової сенсорної мережі - Морковін, Є. О.; Морковін, О. О. (My University, 2019)
The review of the basic principles of building a robust wireless sensor network, through an approach to the assessment of reliability based on the representation of wireless sensor network as markovski process and involves the use of mathematical models of reliability of data transmission between two nodes wsn, which, in turn, is a composition models the reliability of the nodes, the communication between them and the mechanism of their access to the environment.
Keywords: сенсорна мережа; sensor network